Suizidales Verhalten im jungen Erwachsenenalter: Risikofaktoren im Entwicklungsverlauf von der frühen Kindheit bis zum Jugendalter - Buchmann, Arlette; Blomeyer, Dorothea; Laucht, Manfred (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2012)
Suicidal Behaviors Among Young Adults: Risk Factors During Development from Early Childhood to Adolescence Suicidal behaviors are prevalent among young people. Numerous risk factors have been implicated in their development. In the framework of the longitudinal Mannheim Study of Children at Risk, 311 young adults (143 males, 168 females) aged 19-23 years were investigated in order 1) to determine the significance of different risk factors during development in predicting suicidal behaviors in young adulthood, 2) to identify potential risk factors discriminating between suicidal ideation and suicide attempts, and 3) to examine whether the effect of early risk factors was mediated by later occurring predictors. Young adults with suicidal behaviors displayed a number of abnormalities during development, including high load of early family adversity, suicidal ideation and psychiatric problems in childhood and adolescence, as well as low self esteem, poor school functioning, higher levels of novelty seeking, and enhanced affiliations with deviant peers in adolescence. Independent contributions to predicting suicidal behaviors in young adults were provided by early family adversity, suicidal ideation during childhood and adolescence, and low self esteem (with regard to suicidal ideation) and novelty seeking (with regard to suicide attempt), respectively. The impact of early adversity was mediated by child and adolescent externalizing disorders and low self esteem in adolescence. Possible implications of these findings for the prevention and treatment of suicidal behaviors are discussed.